P-96 My care choices register – building an EPaCCS for the future. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Clifton, Tim
Abstract : Background: In 2013, St Helena was commissioned to implement an EPaCCS (National End of Life Care Intelligence Network, 2013) solution across North East Essex that would be used to capture the choices of patients deemed to be in the last 12 months of life. These would be made available at point of care. St Helena launched the My Care Choices Register (MCCR). It quickly became nested within the locality. However, the system procured had limitations and following stakeholder consultation it was decided that a bespoke solution was required. Aims: Reduce administrative overheads; Create a solution that provides value for money, has scope for future development and integrates with GPSoC; Ensure this system can be expanded for use across the healthcare system and aligns with LDR Universal Capabilities. Method: March 2017- after engaging stakeholders, St Helena created a specification for a new solution. Care IS, a clinical solutions developer with a large user base in North East Essex, was approached. Care IS agreed to develop the solution and offer this to other localities in the UK to aid commercial viability. September 2018 – New integrated MCCR is launched. Results: Record duplication issues have been eliminated. The replacement system is now utilised by more health care professionals and areas such as the Ambulance Service. The increased usage has led to a larger number of people dying in their preferred place of care. Conclusion: The integrated nature of MCCR and the increased usage have made it one of the success stories for North East Essex CCG. This is only the start. Phase Two will see MCCR expanded into social care, along with other localities currently in the planning stages to use MCCR across their footprint.